The Autoimmune Profiles in the Etiopathogenesis of Granulomatous Lobular Mastitis - Lu Xie; Jiamei Feng; Qingqian Gao; Wenchao Qu; Shijun Shao; Jiaye Sun; Xueqing Wu; Hua Wan (Immunobiology)
Objectives: Granulomatous lobular mastitis (GLM) is a chronic breast inflammation with low remission and high recurrence. This study aimed to investigate GLM patients' autoimmune profiles and their correlation with GLM etiopathogenesis. Methods: Samples from GLM patients and fibroadenoma (FA) controls admitted to Shuguang Hospital between July 2021 and July 2022 were analyzed. Patients (107 GLM, 73 FA) underwent humoral immunity (C3, C4, IgG, IgM, IgE and IgA), cellular immunity (CD3+CD4+ T cells, CD3+CD8+ T cells, regulatory T cells and CD4/CD8 ratio) and cytokines (IL-1β, IL-6, IL-8, IL-10, IL-12 and TNF-α) tests. Immunohistochemical staining (10 GLM, 10 FA normal tissues) detected IL-1β, IL-6, CD86 and CD206, and immunofluorescence (3 GLM, 3 FA normal tissues) evaluated CD86 and CD206 expression. Multivariate analysis was done using logistic regression. Results: GLM featured granulomas with non-caseation necrosis and inflammatory cell infiltration. GLM patients showed higher C3 (P < 0.001), C4 (P < 0.001), IgE (P < 0.05), IgA (P < 0.05), IL-6 (P < 0.001), and IL-8 levels (P < 0.05). M1 (CD86) and M2 (CD206) macrophage markers were significantly higher in GLM than controls in both immunohistochemical and immunofluorescent staining (P < 0.05). The multivariate logistic regression analysis revealed that reproductive history (OR = 7.011, P < 0.01) and C3 expression level (OR = 5565.570, P < 0.001) were independent factors of GLM. Conclusions: The results highlighted the crucial role of elevated M1 and M2 macrophages in GLM inflammation. GLM was associated with reproductive history, C3, C4, IgE, IgA, IL-6, and IL-8, with reproductive history and C3 as independent risks.